The Indian Removal Act and the Trail of Tears - Hamen, Susan E. (Expansion of our nation., 2019)
Describes the expansion of the United States, focusing on the settlers' conflicts with American Indian nations. Discusses broken treaties, acculturation, the work of U.S. Presidents Thomas Jefferson and Andrew Jackson, the Indian Removal Act, and the Trail of Tears. Also discusses how settlers moving into these lands brought slaves with them to work the land, beginning an era of slaveholding in the new nation. Includes a quiz with answer key, a glossary, color illustrations, and further resources.